Seasonal, annual, and inter-annual Spiniferites cyst production: a review of sediment trap studies. (20th December 2018) - Pospelova, Vera; Zonneveld, Karin A. F.; Heikkilä, Maija; Bringué, Manuel; Price, Andrea M.; Esenkulova, Svetlana; Matsuoka, Kazumi
Abstract: Despite the fact that dinoflagellate cysts of the diverse genus Spiniferites are abundant in coastal and estuarine sediments worldwide, little is known about patterns of their seasonal or annual production. In this paper we review previously published data on Spiniferites cyst fluxes from eight sediment trap time series in estuarine (the Strait of Georgia, Saanich Inlet, Hudson Bay, Omura Bay), coastal (the Santa Barbara Basin, the Arabian Sea), and offshore (off Cape Blanc) environments. This is the first study that provides detailed inter-site comparison of dinoflagellate cysts in sediment traps and analyzes seasonal, annual, and inter-annual cyst production from different geographic regions. We identified that cyst fluxes of all Spiniferites species at a given location increased or decreased simultaneously in all studied sediment trap records. This indicates that different Spiniferites species react in a similar way to local environmental triggers at each site. Average daily total cyst fluxes recorded in the sediment trap time series and in the dated surface sediment samples are greater in coastal and estuarine waters where marine primary productivity is higher. This implies that nutrient availability might be an important factor stimulating Spiniferites production. There is no uniform seasonal pattern in Spiniferites fluxes, but the timing of elevated total Spiniferites fluxes coincided with intervals of local seasonal environmental change at each site. Analyses of all sediment traps revealed that intervals with the highest total Spiniferites fluxes correspond to the timing and intensity of local environmental change at the sea-surface when waters had: minimal turbidity, some water column stability or stratification, availability of nutrients, and sea-ice free conditions. The multi-year trap data record considerable inter-annual variability in Spiniferites fluxes and seasonality when environmental conditions between the years varied. A combination of factors and specific environmental conditions are required to enhance Spiniferites cyst production in each region.